Container Preference of the Asian Tiger Mosquito (Aedes albopictus) in Kathmandu and Lalitpur Districts of Nepal - Gautam, Ishan; KC, Aradhana; Tuladhar, R; Pandey, Basu Dev; Tamrakar, Anand Shova; Byanju, Reena; Dhimal, Meghnath; Aryal, Krishna; Kuch, Ulrich (Journal of Natural History Museum, 2015)
In various countries the Asian Tiger Mosquito (Aedes albopictus) is a known vector of dengue and chikungunya viruses and other pathogens, but its ecology and role in disease transmission in Nepal has not been studied yet. Here, we report on an investigation of the seasonal distribution of potential artificial breeding habitats of A. albopictus in urban areas of the Kathmandu and Lalitpur districts of Nepal. Larval collections were performed from April 2009 to March 2010 simultaneously in all the wet containers present in and around the houses of the study areas. Altogether 1873 water containers in Kathmandu district and 1807 in Lalitpur district were searched in 12 months, out of which 107 (5.7%) and 129 (7.1%), respectively, were found positive for A. albopictus breeding. Within the urban agglomeration of both districts, the breeding was found to vary between localities. Immature stages of A. albopictus were recorded in pre-monsoon, monsoon and post-monsoon seasons as 1.9%, 6.7% and 5.6%, respectively, in wet containers in Kathmandu district. In Lalitpur district, A. albopictus larvae were detected in 4.6%, 7.6% and 7.1% of the wet containers in the pre-monsoon, monsoon and post-monsoon, respectively. The breeding preference ratio during all seasons was highest for discarded tires lying outdoors in both Kathmandu and Lalitpur districts. Among nine container types searched and examined, 95% of discarded tires were found positive for A. albopictus larvae and pupae, followed by metal drums (2%) and plastic drums (1.25%). Continued and increased urbanization and vehicle movement in Kathmandu and Lalitpur districts have resulted in increased amounts of non-biodegradable containers such as tires around human dwellings, thereby creating ideal breeding habitats for A. albopictus. J. Nat. Hist. Mus. Vol. 26, 2012: 181-193